Flagman and Risk Involved in Road Construction Site - Ganapthy, Vigneswara Rao; Subramaniam, Siva Kumar; Mohamad Diah, Abu Bakar; Suaidi, Mohamad Kadim; Hamidon, Abdul Hamid (International Journal of Sustainable Construction Engineering and Technology, 2011)
Road construction is a necessary process of development for the comfort and safety of users. Most road construction is a tidies job whereby the duration and safety is always considered very important for the construction management. One of the most crucial factors in a road construction site is the safety of the road users and the construction workers. Proper safety sign and indication system should be utilized to ensure safety to be optimized. The most common practice of safety indication is performed by traffic controller or also known as the flagman. This practice is very crucial in a road construction site in ensuring the smoothness of the road traffic operation and to alert the road users on road construction activity. This paper highlights the risk factor of flagman in certain road construction or road maintenance site. The risk of fatal accidents is high for the flagman since he is placed in the highest risk zones. Authorities and contractors seek for various methods and measures in eliminating the usage of flagman, yet it is impossible since the usage of flagman is considered the best practice around the globe. The research highlights that the usage of a flagman can be replaced by implementing new technologies to automate the task of controlling the traffic flow without human intervention. The intelligent traffic light system which is proposed in this paper can be wisely utilized to overcome problems arising on the safety measures in a road construction site and also in the afford to be in line with the requirements of Department of Occupational Safety and Health (DOSH) and Ministry of Works to reduce fatal accidents.